What are the risks of using donor breast milk in preterm or low‐birth‐weight neonates?. Issue 1 (January 2018) - Marshburn, Rebecca; Sineath, Marvin
Abstract : EVIDENCE‐BASED ANSWER : Neonates receiving donor breast milk gain about 2.6 g/kg less per day and grow about 1.4 mm less per week in length and 1.2 mm less per week in head circumference than formula‐fed infants in the hospital but have about one‐third the risk of necrotizing enterocolitis compared with formula‐fed neonates (SOR: A, metaanalysis of RCTs). Donor breast milk‐fed neonates are about 20% more likely to receive some breastfeeding on discharge from the neonatal intensive care unit (NICU) (SOR: B, meta‐analysis of cohort studies and single RCT).